A dança dos orixás de Augusto Omolu e suas confluências com a antropologia teatral - Ferreira Junior, Antonio Marcos (2011)
The focus on this work is based on the Orixá´s Dance developed by Augusto Omolu in a transcultural perspective that combines the principles of formation that belongs to Eugenio Barba´s Theatrical Anthropology and utilized by actors and dancers. Here, I present the results of this Field research that occurred on Salvador (Bahia´s State Capital) on the first semester of 2010. It is divided in four parts: The First part begins ―Through me‖; Experiences; living (among others); tensions; I present those impressions, sensations of a personal process with a large amount of subjectivity. I also made an analysis and presented in the process of my artistic development and social-psicophysical. It goes from body weirdness (strangeness of body´s behavior) and methods, to the creation (incorporated) of my own way to participate and execute the gestures and methods normally used on physical preparation. On second part of this research, I present the master´s speach using transcriptions of his classroom allowing to observe and understand the way he absorved and reorganized the theatrical antropology and how he applies it on body´s principles that were absorved from candomblé´s dance. In the third part "Orixá´s dance; Theatrical Anthropology; Actor/ Dancer - Triangulo love" I present the theatrical Anthropology´s concept over the Eugenio Barba´s Speach (teachings) such as some of his followers regarding to energy, dilatation, body issues, resistance and training. On fourth part I present a brief historiography of cultural formation on Brazilian´s Candomblé, and pinpoint their nations natural providers as responsable for an authentic Brazilian religious and artistic culture. At the end of this work I defend the legitimacy and consistence of Master Augusto Omolu´s proposal, that elaborated a Dance technique that offers social - psicophysics and artistic conditions to researchers and artists to analyse and develop several works through a Brazilian Dance with an Africa Essence and begining.